Capsule Endoscopy to Detect Normally Positioned Duodenal Papilla: Performance Comparison of SB and SB2. (4th April 2012) - Park, Sanghoon; Chun, Hoon Jai; Keum, Bora; Seo, Yeon Seok; Kim, Yong Sik; Jeen, Yoon Tae; Lee, Hong Sik; Um, Soon Ho; Kim, Chang Duck; Ryu, Ho Sang
Abstract : Purpose . PillCam SB2 capsule endoscopy, an upgraded version of widely used SB capsule endoscopy, was examined for its performance by comparing with SB. Methods . Examinees with various indications were enrolled for SB2 capsule endoscopy; subjects were also enlisted for the old SB capsule endoscopy. Number of photo images containing papilla of Vater was counted. Shape of the papilla seen in each image was evaluated by scoring 3 (fully observable papilla), 2 (more than half outline), or 1 (less than half outline) points. Images obtained from SB and SB2 were also subjectively compared; resolution and brightness were scored by six experienced endoscopists. Results . Baseline characteristics of two study groups (n = 30 each) were not significantly different. Number of images of the papilla revealed to show similar results between SB (3.1 ± 1.1, range 1 5) and SB2 (3.1 ± 1.5, range 1 8) (P = 0.62 ). The maximum points of outline of papilla evaluated from each subject were also similar between two groups. New SB2 revealed to be superior to SB in terms of resolution but not significantly different in brightness. Conclusion . Our study showed that superiority of SB2 over SB is rather marginal on examining duodenal papilla.